2006
DOI: 10.1038/modpathol.3800528
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic evaluation of the basal-like subtype of invasive breast carcinoma

Abstract: Microarray profiling of invasive breast carcinomas has identified five distinct subtypes of tumors (luminal A, luminal B, normal breast-like, HER2 overexpressing, and basal-like) that are associated with different clinical outcomes. The basal-like subtype is associated with poor clinical outcomes and is the subtype observed in BRCA1-related breast cancers. The aim of this study was to characterize the histologic and immunophenotypic properties of breast basal-like carcinomas that were first positively identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

71
762
7
48

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 935 publications
(888 citation statements)
references
References 23 publications
71
762
7
48
Order By: Relevance
“…In particular, basal-like breast cancers defined using expression profiling are found to be negative for ER and c-erbB2, and positive for vimentin, EGFR, cytokeratin 8/18, and cytokeratin 5/6 on immunohistochemistry. 36 Our results reinforce the association between these immunohistochemical markers in our series of breast cancers in young women, and also corroborate our previous finding of conservation of molecular subtypes in women of Asian ethnicity. 37 In summary, our study confirms the association of basal cytokeratins and vimentin with adverse pathologic features in our series of young women with breast cancer, with our in vitro work lending support to our conclusions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, basal-like breast cancers defined using expression profiling are found to be negative for ER and c-erbB2, and positive for vimentin, EGFR, cytokeratin 8/18, and cytokeratin 5/6 on immunohistochemistry. 36 Our results reinforce the association between these immunohistochemical markers in our series of breast cancers in young women, and also corroborate our previous finding of conservation of molecular subtypes in women of Asian ethnicity. 37 In summary, our study confirms the association of basal cytokeratins and vimentin with adverse pathologic features in our series of young women with breast cancer, with our in vitro work lending support to our conclusions.…”
Section: Discussionsupporting
confidence: 92%
“…A similar trend has been observed in many recent reports which showed that basal-like tumors expressed EGFR (HER1). 28,31,32 Coexpression of HER-1, HER-2 and HER-3 was demonstrated to have a negative synergistic effect on patient outcome. 33 These studies further showed that expression of basal cytokeratins and vimentin are associated with more aggressive tumor features and poorer disease prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our morphologic review, and immunohistochemical stains revealed almost identical findings as reported by Livasy et al 5 The tumors were all high grade (Nottingham score 9/9), with variable geographic necrosis, moderate to good microscopic circumscription and significant lymphoid inflammatory cell infiltrates The tumors were also positive for EGFR (94%) and vimentin (100%). Staining for other sensitive and specific myoepithelial markers (SMA, C-kit, p63) was seen in less than 50% of cases, which indicates that these tumors demonstrate a partial myoepithelial phenotype.…”
Section: Discussionsupporting
confidence: 84%
“…Our study confirms and extends the previously reported findings of the basal-like carcinoma immunophenotype. [5][6][7][8]10 In addition, we demonstrate the presence of in situ carcinoma as the likely precursor lesion for invasive basal-like carcinoma.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation